2006
DOI: 10.1113/jphysiol.2006.118380
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of nitric oxide by rat cerebellar slices

Abstract: Nitric oxide (NO) functions as an intercellular messenger throughout the brain. For this role to be performed efficiently, there must be a mechanism for neutralizing NO, but whether an active biological process exists, or whether NO is lost mainly through diffusion is unclear. To investigate this issue, rat cerebellar slices were exposed to constant levels of NO and the cGMP generated within the slice used as an indicator of NO concentrations therein. NO was about 1000-fold less potent in slices (EC 50 , 1 μM)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
76
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(80 citation statements)
references
References 58 publications
(86 reference statements)
4
76
0
Order By: Relevance
“…From the analysis, it was concluded that the above hypothesis was fully supported, subject to 2 main conditions: first, that the number of active nNOS neurons under low-leptin conditions is half or less than that present in the fully active state achieved after leptin treatment ( Figure 1C), and second, that NO was subject to a similar rate of inactivation to that found in the cerebellum (27) (see Supplemental Results). Accordingly, the model supports the idea that leptin treatment can switch the mode of operation of NO from being active only locally to being a "volume transmitter" capable of influencing cells located at a distance, irrespective of anatomical connectivity ( Figure 2C).…”
Section: Introductionmentioning
confidence: 83%
“…From the analysis, it was concluded that the above hypothesis was fully supported, subject to 2 main conditions: first, that the number of active nNOS neurons under low-leptin conditions is half or less than that present in the fully active state achieved after leptin treatment ( Figure 1C), and second, that NO was subject to a similar rate of inactivation to that found in the cerebellum (27) (see Supplemental Results). Accordingly, the model supports the idea that leptin treatment can switch the mode of operation of NO from being active only locally to being a "volume transmitter" capable of influencing cells located at a distance, irrespective of anatomical connectivity ( Figure 2C).…”
Section: Introductionmentioning
confidence: 83%
“…NO can be broken down by several enzymes, including, in a cyanide-sensitive manner, CcO itself (Cooper et al 1997;Palacios-Callender et al 2007b). In cerebellar slices, however, an unknown cyanide-insensitive process predominates (Hall & Garthwaite, 2006) and exhibits Michaelis-Menten kinetics with a K m of ∼10 nM; for simplicity we assume that this process is independent of oxygen concentration. The different NOS isoforms have different kinetic characteristics.…”
Section: J Physiol 58615mentioning
confidence: 99%
“…The activity of each isoform depends on [O 2 ], and iNOS also shows feedback inhibition by NO which is competitive with O 2 (Santolini et al 2001). Ignoring any basal NO production, the profile of NO across a slice in which iNOS is active can therefore be generated by solving eqn (6), where D NO is 1.98 × 10 −3 cm 2 min −1 (Malinski et al 1993b) and K inact is 10 nM (Hall & Garthwaite, 2006). (6) where (7) gives K NO,iNOS = 1.19 μM.…”
Section: J Physiol 58615mentioning
confidence: 99%
See 1 more Smart Citation
“…Although the NO reductase activity of the enzyme is too slow to constitute a physiological mechanism for the removal of NO (22), there is strong evidence in favor of the oxidation of NO to NO 2 Ϫ both by the purified enzyme (23,24) and by cells (25). Nevertheless, the possibility that cytochrome c oxidase constitutes a significant metabolic route for NO remains controversial (26,27) and has been directly challenged (28).…”
mentioning
confidence: 99%